PERENCANAAN PEMBELAJARAN GURU DI SMA NEGERI 1 MALUA KABUPATEN ENREKANG - Ampry, Evy Segarawati (Pascasarjana Universitas Negeri Makassar, 2017)
Teacher performance in school organizations is basically determined by the ability and willingness of teachers to participate in supporting the teaching and learning process. This factor is the potential of teachers to be able to carry out their tasks to support the needs of educational facilities in schools. The purpose of this study was to determine teacher learning planning at SMA Negeri 1 Malua, Enrekang Regency. The location of this research is at SMA Negeri 1 Malua, Enrekang Regency. The main data sources in this study are the Principal, Physics Teacher and Students. Data collection techniques used are observation, interviews, and documentation. The collected data was then analyzed with qualitative descriptive methods, namely: data reduction, data presentation, and data verification. The results showed that the Planning of Teacher Learning in SMA Negeri 1 Malua, Enrekang Regency which included formulating objectives, choosing the priority of the material to be taught, choosing and using methods, selecting and using existing learning resources, choosing and using learning media that had run according to the rules.